Reproductive modes in populations of late-acting self-incompatible and self-compatible polyploid Ludwigia grandiflora subsp. hexapetala in western Europe - Stoeckel, Solenn; Becheler, Ronan; Portillo-Lemus, Luis; Harang, Marilyne; Besnard, Anne-Laure; Lassalle, Gilles; Causse-Védrines, Romain; Michon-Coudouel, Sophie; Park, Daniel J.; Pope, Bernard J.; Petit, Eric J.; Barloy, Dominique (Peer Community Journal)

(untitled)
Reproductive mode, i.e., the proportion of individuals produced by clonality, selfing and outcrossing in populations, determines how hereditary material is transmitted through generations. It shapes genetic diversity and its structure over time and space, which can be used to infer reproductive modes. Ludwigia grandiflora subsp. hexapetala (Lgh) is a partially clonal, polyploid, hermaphroditic, and heteromorphic plant that recently colonized multiple countries worldwide. In western Europe, individuals are either self-incompatible caused by a late-acting self-incompatibility (LSI) system developing long-styled flowers, or self-compatible (SC), with short-styled flowers. In this study, we genotyped 53 long- and short-styled populations newly colonizing France and northern Spain using SNPs to estimate rates of clonality, selfing and outcrossing. We found that populations reproduced mainly clonally but with a high diversity of genotypes along with rates of sexuality ranging from 10% up to 40%. We also found evidence for local admixture between long- and short-styled populations in a background of genetic structure between floral morphs that was twice the level found within morphs. Long- and short-styled populations showed similar rates of clonality, but short-styled populations presented significantly higher rates of selfing, as expected considering their breeding system and despite the small rates of failure of the LSI system. Within the 53 studied populations, the 13 short-styled populations had fewer effective alleles, lower observed heterozygosity, and higher inbreeding coefficients, linkage disequilibrium and estimates of selfing than what was found in long-styled populations. These results emphasize the necessity to consider the variation of reproductive modes when managing invasive plant species. The overall maintenance of higher genetic diversity with the possibility of maintaining populations clonally in the absence of compatible partners may explain why long-styled individuals seem to be more prevalent in all newly expanding populations worldwide. Beyond Lgh, our methodological approach may inspire future studies to assess the reproductive modes in other autopolyploid populations.